Effect of Thyroid Disorder in Polycystic Ovarian Syndrome in the Women of Diyala Province - Abdulmajeed, Alzahraa Ibrahim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Background: Polycystic ovarian syndrome (PCOS) is the most endocrine disorder common effect (5-10) % in women at reproductive age. Thyroid dysfunction with PCOS is both representing parts of the endocrine system; this link leads to problems of ovulation and pregnancy. Aims: to investigate the prevalence of thyroid disorder in PCOS woman, and associate the outcome with obesity. Patient and method: This study was conducted in Al-batol Teaching Hospital in Baquba City /Iraq. The results reviewed included 63 women: 45 PCOS were diagnosed on the basis of Rotterdam criteria, 18 as control, aged 17- 44 year. The samples have been collected at second day of menstrual cycle, to test fT3, fT4, fTSH in serum. Information was collected for (Age, BMI, LH, and FSH) to be part of this study. Results: A significant increasing in fT3 was found in PCOS women comparison with control pvalue>0.05. T3 showed in significant differences between lean PCOS matched against control Pvalue < 0.05, along with statistically increasing of TSH level in (lean, overweight) PCOS comparison with control pvalueË‚0.05. Conclusion: PCOS is associated with hypothyroidism. Obesity or overweight is a key factor leads to increased risk of thyroid disorder.